CORRELATION BETWEEN SELF CONCEPT AND DEFENCE MECHANISM OF STUDENTS - Yusri, Fadhilla (Universitas Muhammadiyah Metro, 2016)
Basically every individual has a concept about himself. The concept which has been ingrained in each individual, would influence the behavior of that individuals in various aspects of their life including in facing the problems. Only a little of the students are able to solve the problem well. Sometimes to keep themselves right in a problem, they “form” defense mechanism. This research was conducted to reveal the correlation between self concept and defense mechanism of guidance and counseling students of IAIN Bukittinggi. The population was the entire of guidance and counseling students that concist of 452 students, and 102 samples. The data was collected by using questionnaire that was processed using product moment technique in SPSS 21.0 version. The result shown that there is a significant correlation between self-concept and defense mechanism in facing the problem with the r calculated was 0.433. The strength of the correlation between self-concept and defense mechanism of BK students of IAIN Bukittinggi are at moderate or sufficient.